Penyuluhan Bijak Bermedia Sosial Pada Masyarakat di Desa Tarasu Kabupaten Bone Provinsi Sulawesi Selatan - Abdul Rahman; Nurlela Nurlela; Najamuddin Najamuddin (Jurnal Pengabdian UNDIKMA, 2020)
This service activity aims to provide understanding to the community, especially teenagers in Tarasu Village to be smart and careful in spreading and responding to news spread on social media, especially Facebook. The methods used are lectures, question and answer, and discussion. The material presented was the introduction of institutions, socialization of the Law on Information and Electronic Transactions (UU ITE), socialization of filters before sharing, delivery of wise social media methods, and screening of short films. This activity received a warm welcome and was followed enthusiastically by the community. Teenagers understand that using Facebook must pay attention to ethics. Thus, media literacy is an effort to educate adolescents in using social media as well as the legal consequences that can be accepted when abusing social media.